2018
DOI: 10.1016/j.virusres.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of K22 against members of the order Nidovirales

Abstract: Recently, a novel antiviral compound (K22) that inhibits replication of a broad range of animal and human coronaviruses was reported to interfere with viral RNA synthesis by impairing double-membrane vesicle (DMV) formation (Lundin et al., 2014). Here we assessed potential antiviral activities of K22 against a range of viruses representing two (sub)families of the order Nidovirales, the Arteriviridae (porcine reproductive and respiratory syndrome virus [PRRSV], equine arteritis virus [EAV] and simian hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…187 RNA synthesis inhibitors, which reduce the formation of double-membrane vesicles, a hallmark of CoV2 replication, have been identified as potential antiviral drugs. 188,189 A double-stranded RNA activated caspase oligomerizer (DRACO) that targets long viral double-stranded RNA and induces apoptosis of infected cells, but spares healthy cells, might also be useful in the treatment of CoVs. 190…”
Section: Rna Synthesis Inhibitorsmentioning
confidence: 99%
“…187 RNA synthesis inhibitors, which reduce the formation of double-membrane vesicles, a hallmark of CoV2 replication, have been identified as potential antiviral drugs. 188,189 A double-stranded RNA activated caspase oligomerizer (DRACO) that targets long viral double-stranded RNA and induces apoptosis of infected cells, but spares healthy cells, might also be useful in the treatment of CoVs. 190…”
Section: Rna Synthesis Inhibitorsmentioning
confidence: 99%
“…This should also reduce the risk of animal losses due to opportunistic infections such as fulminating pneumonia in young foals. Only a recent study, exploring the inhibition of nidoviruses by the broad-spectrum antiviral molecule K22 in infected hamster cells (BHK-21), reported the first evidence of EAV inhibition by a synthetic molecule 29 . The identification of BSA was until now impeded by the lack of suitable assay for monitoring EAV growth in high-throughput settings.…”
Section: Discussionmentioning
confidence: 99%
“…Following a screening which aimed at identifying anti-HCoV-229E compounds, we have described a potent small-compound inhibitor, K22, which efficiently inhibited coronavirus replication and was recently shown to additionally inhibit a wide range of virus species within the families Coronaviridae and Arteriviridae ( 12 , 13 ). K22 has been shown to act on early postentry stages of coronavirus replication and to target membrane-bound RNA synthesis by interfering with the establishment of virus-induced replicative structures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, K22 inhibited a broad range of coronaviruses from several phylogenetic lineages (alpha-, beta-, and gammacoronaviruses), including murine hepatitis virus (MHV), type I feline coronavirus (FCoV), and avian infectious bronchitis virus (IBV), as well as the highly pathogenic human severe acute respiratory syndrome-associated coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) ( 12 ). Furthermore, it was recently reported that K22 impairs the replication of not only viruses in the Coronavirinae subfamily but also members of the Torovirinae subfamily, such as white beam virus (WBV; genus Bafinivirus ) and equine torovirus (EToV; genus Torovirus ), as well as porcine reproductive and respiratory syndrome virus (PRRSV) and equine arteritis virus (EAV), which are representative arteriviruses ( 13 ).…”
Section: Introductionmentioning
confidence: 99%